Tradisi Kenduri dalam Penguatan Toleransi Antar Umat Muslim dan Katolik di Kampung Menciran Yogyakarta - Putra, Rodhy Baskara (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2023)
The Kenduri tradition in Kampung Menciran, Kebonagung Village, Bantul, Yogyakarta, is a form of local wisdom that plays an important role in maintaining and strengthening interfaith tolerance, particularly between Muslims and Catholics. This study aims to analyze how the Kenduri tradition contributes to fostering relationships between Muslims and Catholics in Kampung Menciran and how it serves as an effective social instrument in creating a peaceful and harmonious atmosphere. The findings reveal that the Kenduri tradition in Kampung Menciran has a profound role and serves as a medium of communication between Muslims and Catholics. The Kenduri rovides a platform for the community to connect, interact, and strengthen solidarity.